2013
DOI: 10.1159/000343852
|View full text |Cite
|
Sign up to set email alerts
|

From Cirrhosis to Hepatocellular Carcinoma: New Molecular Insights on Inflammation and Cellular Senescence

Abstract: Sequential progression from chronic liver disease to fibrosis and to cirrhosis culminates in neoplasia in hepatocellular carcinoma (HCC). The preneoplastic setting of the cirrhotic background provides a conducive environment for cellular transformation. The role of classical inflammation in cirrhosis is widely known, but the exact mechanism linking inflammation and cancer remains elusive. Recent studies have elucidated roles for NF-κB, STAT3 and JNK as possible missing links. In addition, the “inflammasome” (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(133 citation statements)
references
References 76 publications
2
131
0
Order By: Relevance
“…Given the fact that a single miR targets multiple kinds of mRNA, constitutive activation of multiple molecules may act in concert to restore the sensitivity of HCC to sorafenib [56]. Studies on molecular biology and signal transduction are a key issue to understanding the efficacy of systemic therapy to HCC [57,58,59,60]. …”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that a single miR targets multiple kinds of mRNA, constitutive activation of multiple molecules may act in concert to restore the sensitivity of HCC to sorafenib [56]. Studies on molecular biology and signal transduction are a key issue to understanding the efficacy of systemic therapy to HCC [57,58,59,60]. …”
Section: Introductionmentioning
confidence: 99%
“…Several reports have suggested that hepatocarcinogenesis involves multiple molecular pathways with the accumulation of genetic and epigenetic alterations, including point mutations and abnormal DNA methylation [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this observed activation of NF-κB may be attributed to the fact that HCC commonly arises in a setting of chronic inflammation and subsequent liver fibrosis and cirrhosis (Ramakrishna et al, 2013). It was found that in HBV-induced hepatocarcinogenesis, the oncogenic HBV X protein activates the NF-κB signaling pathway through the upregulation of TANK-binding kinase 1 (TBK1), thus promoting progression of HCC via proliferative and antiapoptotic effects, as well as triggering the spread of tumor cells (Kim et al, 2010 andZhang et al, 2010).…”
Section: Resultsmentioning
confidence: 93%